Energy optimization and economic study of an energy storage system based on a carbon dioxide-to-methanol process. (June 2023) - Shi, Lining; Wang, Chenfang; Liu, Shihao; Cheng, Xiaozhang; Liu, Quan; Zhuge, Weilin; Zhang, Yangjun
Abstract: When hydrogen storage is used for renewable energy generation, it has the advantages of easy access to raw materials, large capacity, and is not limited by terrain factors but faces the disadvantages of difficult hydrogen storage and high losses. This thesis presents a method of hydrogen storage using carbon dioxide hydrogenation to methanol instead of hydrogen storage and transportation. A model of a hydrogen-methanol energy storage system was developed. The performance of the methanol synthesis unit was optimized using measures such as heat integration and heat pumps. The energy consumption and economics of the 108 MW energy storage system were analysed. The obtained results show that the energy efficiency of the energy storage system is 32.2 %. The energy efficiency of the methanol synthesis unit was 61.1 %, and the effective carbon utilization was 94.9 %. The total energy consumption of the hydrogen-methanol energy storage system is 317.56 MW. After heat integration and the addition of heat pumps, the total energy consumption of the CO2 hydrogenation to methanol process was reduced by 58.7 %, including a 33.4 % reduction in heat load and a 66.3 % reduction in cooling load. The heat pump can reduce the heat load by up to 16.2 MW, which is equivalent to 33.8 % of the heat load after heat integration. The total asset investment of the energy storage system is 812.3 yuan/MWh/year. The total asset investment of the methanol synthesis unit is 945.28 yuan/t/year. The price of electricity is the most important factor affecting the economy of the system. The economic benefit of energy storage systems decreases as the price of electricity decreases. When the electricity price is 0.2 yuan/kWh, the system generation cost is 0.591 yuan/kWh, and the economic benefit becomes positive. Highlights: A hydrogen storage method with methanol as an intermediate medium was presented. A model of a hydrogen-methanol energy storage system was developed. The performance of the methanol synthesis plant was optimized. The energy consumption and economics of the 108 MW energy storage system were analysed.